Mathematical analysis of interconnected photovoltaic arrays under different shading conditions - S.N. Nnamchi; C.O.C. Oko; F.L Kamen; O.D. Sanya (Cogent Engineering, 2018)
A comprehensive mathematical analysis of interconnected photovoltaic arrays under different shading conditions (opacity) and patterns (column, row, diagonal and corner) has been carried out in this work. The equivalent circuit models for the different shading conditions and patterns, and pseudocode algorithm were developed upon which the performance characteristics of the interconnected arrays were analyzed. Five different interconnections were inclusively considered in this work: series-parallel, total-cross-tied (TCT), bridge-linked, ladder and honey-comb interconnection. The emerging analytical results revealed that TCT is most dominant interconnection and shading patterns across the strings (row and diagonal) have detrimental effect on output power, especially when the opacity is one (signifying perfect shading condition) but shading patterns along the string (column or corner shadings) are less severe to power generation. The formation of double peaks sequel to the presence of shadings are inimical to power generated from the interconnected arrays. Moreover, increasing the interconnections enhances the output power and further serves as a means of bypassing current in the event of threats to the modules. Thus, the results obtained provide vital information for smooth operation and maximization of output power in interconnected arrays by avoiding shades on the strings.